Tree Age Distributions Reveal Large-Scale Disturbance-Recovery Cycles in Three Tropical Forests - Vlam, Mart; van der Sleen, Peter; Groenendijk, Peter; Zuidema, Pieter A. (Frontiers in Plant Science, 2017)
Over the past few decades there has been a growing realization that a large share of apparently ‘virgin’ or ‘old-growth’ tropical forests carries a legacy of past natural or anthropogenic disturbances that have a substantial effect on present-day forest composition, structure and dynamics. Yet, direct evidence of such disturbances is scarce and comparisons of disturbance dynamics across regions even more so. Here we present a tree-ring based reconstruction of disturbance histories from three tropical forest sites in Bolivia, Cameroon and Thailand. We studied temporal patterns in tree regeneration of shade-intolerant tree species, because establishment of these trees is indicative for canopy disturbance. In three large areas (140-300 ha), stem discs and increment cores were collected for a total of 1154 trees (>5 cm diameter) from 12 tree species to estimate the age of every tree. Using these age estimates we produced population age distributions, which were analyzed for evidence of past disturbance. Our approach allowed us to reconstruct patterns of tree establishment over a period of around 250 years. In Bolivia, we found continuous regeneration rates of three species and a peaked age distribution of a long-lived pioneer species. In both Cameroon and Thailand we found irregular age distributions, indicating strongly reduced regeneration rates over a period of 10 to 60 years. Past fires, windthrow events or anthropogenic disturbances all provide plausible explanations for the reported variation in tree age across the three sites. Our results support the recent idea that the long-term dynamics of tropical forests are impacted by large-scale disturbance-recovery cycles, similar to those driving temperate forest dynamics.